Ecosystem requirements for composability and reuse: An investigation into ecosystem factors that support adoption of composable practices for engineering design. Issue 4 (1st January 2013) - Oster, Christopher; Wade, Jon
Abstract Composability is a systems architecture and design concept focusing on composing new systems from known components, designs, product lines, and reference architectures as opposed to focusing on "blank sheet" designs based on requirements decomposition alone. The concept of composability has been a goal of the US Department of Defense (DoD) for many years, most recently taking the form of Platform‐based Engineering. Despite this focus, the goal of effective modularity and design reuse has been somewhat elusive in the aerospace and defense sectors. This paper describes an ecosystem construct which incorporates market factors, business practices, and trends that occur in industries where composability and reuse have taken hold in order to identify a path forward for effective adoption of composability in the aerospace and defense marketplace. A number of examples of composable design are described, followed by proposals for necessary changes within the DoD ecosystem to facilitate its support. © 2013 Wiley Periodicals, Inc. Syst Eng 16